2004
DOI: 10.1111/j.1439-0523.2004.01030.x
|View full text |Cite
|
Sign up to set email alerts
|

A dominant gdcP‐specific marker derived from Moricandia nitens used for introducing the C3‐C4 character from M. nitens into Brassica crops

Abstract: Differential localization of decarboxylation and carboxylation in association with Kranz anatomy distinguish species with C 4 or C 3 -C 4 intermediate photosynthesis from species with C 3 photosynthesis. Moricandia nitens has a C 3 -C 4 intermediate photosynthetic mechanism and yet is closely related to C 3 Brassica species. In order to introduce the C 3 -C 4 character from M. nitens into Brassica crops, sesquitetraploids (MACC) were synthesized by crossing Brassica napus (AACC) and a somatic hybrid (M. nitens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In this family, interspecific and intergeneric crosses are relatively easier to achieve than in other families (e.g., Bang et al, 1996Bang et al, , 2003reviewed in Matsuzawa et al, 1996). As a result, studies of artificial hybridization between C 3 and C 3 -C 4 intermediate species in this family have been attempted to genetically improve carbon and water economies by the introduction of C 3 -C 4 intermediate characteristics into C 3 plants (Apel et al, 1984;O' Neill et al, 1996;Razmjoo et al, 1996;Rawsthorne et al, 1998;Yan et al, 1999;Zhang et al, 2004). In an early study, Apel et al (1984) reported that hybrids showed Γ values intermediate between those of the parent C 3 plants and C 3 -C 4 intermediate species.…”
mentioning
confidence: 99%
“…In this family, interspecific and intergeneric crosses are relatively easier to achieve than in other families (e.g., Bang et al, 1996Bang et al, , 2003reviewed in Matsuzawa et al, 1996). As a result, studies of artificial hybridization between C 3 and C 3 -C 4 intermediate species in this family have been attempted to genetically improve carbon and water economies by the introduction of C 3 -C 4 intermediate characteristics into C 3 plants (Apel et al, 1984;O' Neill et al, 1996;Razmjoo et al, 1996;Rawsthorne et al, 1998;Yan et al, 1999;Zhang et al, 2004). In an early study, Apel et al (1984) reported that hybrids showed Γ values intermediate between those of the parent C 3 plants and C 3 -C 4 intermediate species.…”
mentioning
confidence: 99%
“…Our previous studies indicated that great variations were found in the 5 -flanking regions of the P protein gene among the C 3 -C 4 species, M. nitens, and 2 C 3 species, B. napus and Arabidopsis. In addition, conserved DNA regions specific to C 3 species were also revealed although B. napus and M. nitens have closer revolutionary relationship than B. napus and Arabidopsis (Zhang et al, 2004). This implies that further investigation of regulatory sequences of P protein gene conserved in C 3 species in Brassicaceae might shed light on understanding the mechanism of C 3 -C 4 photosynthesis and even on the evolutionary process of C 3 -C 4 species in this family.…”
Section: Research Reportmentioning
confidence: 94%
“…Previous studies indicated that the lack of P protein in the mesophyll cells of C 3 -C 4 species from Flaveria is regulated by differential transcription of the P protein gene (Bauwe et al, 1995). Additionally, our previous results indicated that conserved DNA regions in C 3 species (Arabidopsis and B. napus) in the promoter regions of the P protein gene were revealed (Zhang et al, 2004). All this information implies that the lack of P protein from the mesophyll cells of Moricandia (C 3 -C 4 species) may also be regulated by differential transcription.…”
Section: Research Reportmentioning
confidence: 95%
See 1 more Smart Citation
“…This compartmentalization has been used to reduce the carbon loss by inhibiting the metabolism of glycine in the mesophyll cell, allowing it to be recovered in the bundle sheath cells. A dominant marker gdcP was developed from the gdc gene for C 3 -C 4 intermediate phenotype in the integration of into B. napus using a M. nitens  B. olereaca somatic hybrid (Zhang et al 2004).…”
Section: Introductionmentioning
confidence: 99%